TRANSCENDENTAL COMMUNICATION BETWEEN MAN AND GOD IN PRAYER SERVICES: HAROLD LASSWELL'S PERSPECTIVE - M. Gufran; Muhammad Amrillah (TASAMUH, 2022)
When conducting intrusion with other parties in everyday life, humans always engage in communication activities. In addition to needing communication with fellow creatures, humans also have communication needs with the Creator, namely Allah SWT. This study aims to review the study of prayer and worship as transcendental communication between humans and God from the perspective of Harold Lasswell. This research used the library research method. Any data supporting this study are reviewed descriptively. This research shows that the model of transcendental communication between man and God in the prayer service of Harold Lasswell's perspective can be summed up as follows: First, the communicator. In prayer activities, every Muslim who establishes salat is a communicator who is carrying out transcendental communication activities. Second, Message. Readings are included in every movement of prayer, whether the pillars or the sunnah. These readings are communication messages from Allah SWT's servants. Third, Media. In prayer activities, the medium is the prayer movement itself. Prayer activities that begin with takbir and close with greetings are gestures that can be referred to as channels. Fourth, communicants. In prayer activities, the communicant is Allah SWT; God Almighty hears all the communication messages conveyed by His servants throughout the universe. Fifth, Effect. In the context of prayer worship, the effect is how the reply or reward given by Allah SWT as a communicant in the process of transcendental communication in prayer worship is received. People of faith deserve to be convinced or believe wholeheartedly that every good deed, such as prayer service, must get a good reward on the side of Allah SWT.